Indexing energy and cost of the pretreatment for economically efficient bioenergy generation - Preethi,; M, Gunasekaran; Banu. J, Rajesh (Frontiers in Energy Research, 2023)
The growing necessity for energy worldwide has led to the hunt for an interminable solution in the form of sustainable energy generation. To accomplish sustainability, these problems can be resolved using renewable waste biomass, which is readily accessible and low priced. Moreover, the ecological issue due to the disposal of this waste biomass into the environment is also counteracted by the use of this biomass for energy generation along with the substantial solid reduction for disposal. The presence of complex biopolymers in biomass, which hasten the hydrolysis step during energy generation, was enhanced by the application of a pretreatment method. The efficiency of the pretreatment methods was enhanced by maintaining the cost and energy usage since the commercialization of this method is largely limited. The major economic drivers are based on solid concentration and, thus, lead to higher capital costs. This study reveals the wide assortment of current progression in pretreatment techniques for treating waste biomass with special focus on combined and phase-separated pretreatment. Additionally, it converses the advantages and limitations of pretreatment methods. This pivotal investigation brings about the cost- and energy-effective conversion solution that paves the way for a sustainable energy system.